A between-subjects comparison of same-group and cross-group friendships amongst Coloured South African students at Stellenbosch Univeristy - Lewis, Cindy Lisa (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.